Diagnostic value of motor evoked potential parameters in patients with Parkinson's disease stage II - A. V. Demchenko; Dzh. N. Aravitska (Zaporozhye State Medical University, 2022)
The aim of our study was to identify the most informative parameters of motor evoked potential (MEP) based on clinical and neurophysiological comparisons in patients with Parkinson's disease (PD) stage II. Materials and methods. The study included 90 patients aged 45 to 75 years with stage II PD according to Hoehn-Yahr. Examination of patients was performed according to the following scheme: clinical and neurological examination with MDS UPDRS scale and neurophysiological examination to determine the latency, amplitude and duration of MEP after 4 tests with a gradual increase of magnetic field induction. Our study involved patients with predominantly right and left-sided motor symptoms, so for correct statistical analysis, the dominant side was considered as the debut side or the side with more pronounced motor symptoms, the subdominant side was considered as the opposite one. Results. In cases of patients with stage II PD the MEP latency significantly decreased, and the amplitude and duration of MEP significantly increased in samples with increasing magnetic field induction in the right and left hemispheres of the brain. It was found significant positive moderate correlation between UPDRS part III total score and MEP latency in the ipsilateral premotor cortex to the dominant side of motor symptoms with samples of magnetic induction (1.1 Tl - r = 0.34, P < 0.05; 1.32 Tl - r = 0.32, P < 0.05; 1.76 Tl - r = 0.31, P < 0.05). Also positive mild correlation was found between MEP latency in the ipsilateral premotor cortex to the subdominant side of motor symptoms and UPDRS part III total score (1.54 Tl - r = 0.22, P < 0.05; 1.76 Tl - r = 0.29, P < 0.05). Mild positive correlation (r = 0.29, P < 0.05) was found between MEP duration of ipsilateral premotor cortex to the subdominant side of motor symptoms and UPDRS part III total score in sample with 1.54 Tl magnetic induction. No significant correlations were found to the amplitude parameter and the severity of clinical symptoms in investigated patients with PD stage II. Conclusions. The most informative neurophysiological indicators in patients with PD stage II are the MEP latencies. The MEP latencies of the premotor cortex, which is ipsilateral to the side with more pronounced motor symptoms, have a particularly close relationship with UPDRS part III total score in the samples with 1.10-1.76 Tl magnetic inductions (r = 0.31-0.34, P ˂ 0.05). The MEP duration of premotor cortex, which is ipsilateral to the side with less pronounced motor symptoms, is most closely associated with the severity of motor manifestations on the subdominant side in patients with PD stage II (r = 0.27, P ˂ 0.05).